Retracted publications in medical education: systematic review - Sara Barbosa; Sílvia Paredes; Laura Ribeiro (International Journal for Educational Integrity)
Abstract Introduction Research Integrity is based on fundamental principles, including reliability, honesty, respect and accountability. Practices that threaten these standards are classified as research misconduct and fraud and the resulting publications must lead to retraction. Although research in medical education impacts university policies and influences professionals’ behavior, publication retraction in this field has never been explicitly investigated. The main aim of this study is to examine the characteristics of retracted publications in medical education. Methodology An eletronic search was performed during June 2023 in three databases: PubMed, Web of Science and Scopus, to identify all the retracted publications in medical education research. We extracted the characteristics of the authors, publication journals, citations and retraction notices. Results A total of 12 publications were included in this systematic review. Fifty percent of the publications were published after 2020, being 42% of the studies from China. The average impact factor of the journals was 3.1. Among all the citations found, 54% happened after retraction date and none of them was used as an example of misconduct or to refer to the retraction process. The most common reasons for retraction were duplicate publication (25%) and systematic manipulation of the publication process (25%), followed by peer review concerns (17%). Conclusion This study shows evidence that the number of retracted publications in medical education is increasing. Retraction notices tend to be ambiguous and unclear without enough information regarding the request or the reasons of retraction. All of these findings affect the truthfulness and transparency of medical education research. More efforts need to be done to standardize and improve the retraction notice availability, and researchers, journals, academic institutions and funders have to be more aware and publicise this growing problem, playing a key role to prevent the dissemination of misconduct and fraud in medical education research among the academic and scientific communities.